2013
DOI: 10.1111/apt.12373
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: worldwide variation in the frequency of coeliac disease and changes over time

Abstract: Summary Background Coeliac disease (CD), originally thought to be largely confined to Northern Europe and Australasia and uncommon in North America and the Middle East, is now recognised to be equally common in all these countries. It is still thought to be rare in the Orient and Sub‐Saharan Africa. Aim To assess geographical differences and time trends in the frequency of CD. Methods Medline and Embase searches were conducted on 10 November 2012, from 1946 and 1980 respectively, using the key words: coeliac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
182
4
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(205 citation statements)
references
References 236 publications
8
182
4
9
Order By: Relevance
“…HLA-DQ8, which is present in less than 5% of West Europeans, Americans and Asians, was found in 5%-10% of English, Tunisians and Iranians (14) .…”
Section: Discussionmentioning
confidence: 97%
“…HLA-DQ8, which is present in less than 5% of West Europeans, Americans and Asians, was found in 5%-10% of English, Tunisians and Iranians (14) .…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of both IBS and CD vary, depending on ethnicity and geographical location (7,(70)(71)(72), likely reflecting differences in diet, genetics, and culture. This metaanalysis included studies from multiple countries, recruiting patients of different ethnic origins.…”
Section: Discussionmentioning
confidence: 99%
“…The current prevalence of CD ranges between 1/100-1/500 subjects depending to the different populations surveyed and the method employed, with a higher positive diagnosis in females [2] . The accuracy of CD prevalence has been substantially improved by the high sensitivity and specificity of serological tests detecting anti-endomysial, anti-tissue transglutaminase or antideamidated gliadin antibodies.…”
Section: Epidemiologymentioning
confidence: 99%
“…The pediatric population was not analyzed in these studies, but prevalence of over 1%, even in older populations, is similar to that observed in pediatric studies. A recent systematic review on world CD frequency in recent years, mainly based on European studies, found variable ratios of prevalence and incidence, which was similar, in many cases, between children and adults [2] . Although a hypothesis based on the evolution of pediatric CD towards latency would explain a lower frequency in adults; more studies on the natural evolution of this disease are needed in order to confirm it.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation